Impact of Authentic Leadership on Employee Well-Being in Commodity Market: A Case of Nigeria’s Cocoa Industry - Tayo, Adekunle Michael; Olajide, Olabode; Kutu, Jacob Oloruntoba (Advances in Social Sciences Research Journal, 2024)
This study aims to investigate the relationship between authentic leadership and employee well-being in the Nigerian cocoa sector, a key commodity market in the country. Authentic leadership is characterized by self-awareness, relational transparency, balanced processing, and internalized moral perspective, and has been linked to positive employee outcomes in various contexts. Using a case study approach, this research examined the experiences of employees in the Nigerian cocoa industry to understand how authentic leadership behaviours exhibited by employers and managers influence factors such as organizational commitment, work-life balance, and overall well-being. Data were collected through interviews of Nigeria cocoa sector employees to gain a holistic perspective. Findings revealed that the Nigerian cocoa sectors comply with minimum legal requirements but do not proactively go beyond those standards, and that they provide basic healthcare benefits and adhere to safety regulations but lack comprehensive well-being programs. The findings of this study are expected to contribute to the scholarly literature on authentic leadership and its application in non-Western, developing economy settings. It will also provide practical insights for Nigerian cocoa organisations and policymakers on fostering leadership practices that promote leaders’ authenticity, employee thriving and sustainable business performance. The results may have broader implications for leadership development and human resource management strategies in Nigeria's vital commodity markets.